Outsourcing Recruitment as a Solution to Prevent Discrimination: A Correspondence Study - Clémence Berson; Morgane Laouénan; Emmanuel Valat (Institute of Labor Economics (IZA), 2019)
Many studies have proven the existence of discriminatory behavior from employers according to the origin of applicants. However, little is known about how these behaviors can be prevented. In this work, we assess how organization of recruitment in large companies affects ethnic discrimination. We consider large multi-establishment companies and distinguish two types of recruitment organization: hiring made through a human resources (HR) service at a centralized level of the company and hiring made at only the level of the establishment concerned by the position, generally by managers in charge of recruitment. To conduct our research, we rely on data from a correspondence study conducted in 2016 by the Dares (French Ministry of Labor) in large companies, which shows the existence of ethnic discrimination in hiring. This experimentation allows us to gather precise and original information on the level at which applications were selected for each of the 1,500 tests carried out. Because access to a centralized HR service is potentially endogenous, we use an instrument to assess the causal effect: whether (or not) the establishment with the job offer belongs to a company that has developed a franchise network. Our results indicate that access to a centralized HR service in the selection of applications has an important effect on the level of discrimination: This type of recruitment organization results in a 0.29-point decrease in the probability that the applicant of presumed "French" origin is selected alone.
Keywords: A13; C93; J21; J71; J78; O15; 330; North African origin; large firms; hiring discrimination; organization of human resources